2011
DOI: 10.1111/j.1752-0606.2011.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of Outcome Research on Marital and Family Therapy in Treatment for Alcoholism

Abstract: This review of controlled studies of marital and family therapy (MFT) in alcoholism treatment updates our earlier review (XXXXXXX). We conclude that, when the alcoholic is unwilling to seek help, MFT is effective in helping the family cope better and motivating alcoholics to enter treatment. Specifically, both Al-Anon facilitation and referral and spouse coping skills training (based on new findings) help family members cope better; and Community Reinforcement and Family Training (CRAFT) promotes treatment ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
120
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(131 citation statements)
references
References 78 publications
3
120
0
3
Order By: Relevance
“…This conclusion is based on equivalent or greater improvement in COs' functioning following Al-Anon facilitation or referral than that of waitlist control groups or family-involved treatments. However, no new studies of Al-Anon facilitation and referral have been conducted since 2003 (O'Farrell andClements, 2012). In addition, no previous study has compared the health and coping of Al-Anon newcomers and members, as we did.…”
Section: Al-anon Membersmentioning
confidence: 82%
See 2 more Smart Citations
“…This conclusion is based on equivalent or greater improvement in COs' functioning following Al-Anon facilitation or referral than that of waitlist control groups or family-involved treatments. However, no new studies of Al-Anon facilitation and referral have been conducted since 2003 (O'Farrell andClements, 2012). In addition, no previous study has compared the health and coping of Al-Anon newcomers and members, as we did.…”
Section: Al-anon Membersmentioning
confidence: 82%
“…A LCOHOL USE DISORDERS HAVE NEGATIVE consequences for both drinking individuals and their loved ones (Dawson et al, 2007;O'Farrell and Clements, 2012;Rowe, 2012). Poor functioning by the concerned other person (CO) has a negative impact on the drinking individual and may jeopardize recovery (Rowe, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The social environment has a significant effect on substance use. Research has demonstrated that marriage and a satisfying marital relationship reduce relapse among men with alcohol dependence and that incorporating relationship counselling into treatment for alcoholism leads to improved outcomes, such as abstinence 4 . Conversely, a critical partner, anger and psychological aggression are associated with poorer outcomes such as relapse 5 .…”
Section: A Network Of Supportmentioning
confidence: 99%
“…For example, rates of alcohol and other drug misuse in US personnel increase after deployment (Jacobson et al, 2008), and these problems are well-established predictors of relationship dissatisfaction and interpersonal violence (O'Farrell & Clements, 2012). Similarly, the quality of the couple relationship can impact trauma symptoms in military personnel.…”
Section: A Number Of Western Countries Have Deployed Large Numbers Ofmentioning
confidence: 99%